2020
DOI: 10.3390/cells9102164
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Multi-Omics Analysis in Calcific Aortic Valve Disease Reveals a Link to the Formation of Amyloid-Like Deposits

Abstract: Calcific aortic valve disease (CAVD) is the most prevalent valvular heart disease in the developed world, yet no pharmacological therapy exists. Here, we hypothesize that the integration of multiple omic data represents an approach towards unveiling novel molecular networks in CAVD. Databases were searched for CAVD omic studies. Differentially expressed molecules from calcified and control samples were retrieved, identifying 32 micro RNAs (miRNA), 596 mRNAs and 80 proteins. Over-representation pathway analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 86 publications
(103 reference statements)
1
17
0
Order By: Relevance
“…These observations indicate that physiological fibrinolysis in vivo is interconnected with the formation of TTR amyloid [ 190 ]. Since plasmin activation occurs in vivo at sites of injury (i.e., on vascular and arterial walls or vascular basement membrane), an intersection between TTR amyloid formation and the fibrinolytic system corresponds to previous observations concerning CAVD [ 155 ]. Additionally, cleavage-induced formation of TTR amyloid may lead to local microcalcification in situ due to the binding of Ca 2+ by destabilized TTR molecules [ 47 , 108 ].…”
Section: Ttr and Wound Healing (Fibrinolysis Vs Thrombosis)supporting
confidence: 76%
See 3 more Smart Citations
“…These observations indicate that physiological fibrinolysis in vivo is interconnected with the formation of TTR amyloid [ 190 ]. Since plasmin activation occurs in vivo at sites of injury (i.e., on vascular and arterial walls or vascular basement membrane), an intersection between TTR amyloid formation and the fibrinolytic system corresponds to previous observations concerning CAVD [ 155 ]. Additionally, cleavage-induced formation of TTR amyloid may lead to local microcalcification in situ due to the binding of Ca 2+ by destabilized TTR molecules [ 47 , 108 ].…”
Section: Ttr and Wound Healing (Fibrinolysis Vs Thrombosis)supporting
confidence: 76%
“…The molecular mechanisms of CAVD are similar to those characteristic for pathogenesis of atherosclerosis [ 171 ]. Complex analysis of the transcriptome, proteome, and miRNA datasets differentially expressed in CAVD allowed the creation of a three-dimensional multilayered model of the disease [ 155 ]. The 3D network of interactions of seven input genes, four input miRNAs, and two connectors indicated that two amyloid-forming proteins, amyloid β precursor protein (APP) and TTR, play central roles in the processes underlying CAVD [ 155 ].…”
Section: Ttr Contribution To Cardiovascular Disease and Vascular Calcificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Methylomic, metabolomic, and proteomic data were combined to form a multi-layered network whereby the omic data sources were matched with sources of healthy and calcified aortic valves. The novel networks in this study found associations between amyloid deposits on aortic valves in Alzheimer's patients and highlighted associated genes to the valve spongiosa layer, which has previously not been central to calcific aortic valvular disease research (100). Network methods, specifically deep neural networks, attracted the public eye after Google DeepMind's AlphaFold 2 model predicted protein folded structures using only the amino-acid sequence with near-identical performance as gold standard experimental methods, such as cryo-electron microscopy (101,102).…”
Section: Methodsmentioning
confidence: 75%